(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the public’s demand for seeking health consultation information on Health & Life Newspaper, the official online newspaper of the Vietnamese Ministry of Health. Method: A cross-sectional descriptive study was conducted from January to April 2025 with a sample of 385 participants selected through convenience sampling. Data were collected via a self-administered online questionnaire using the SurveyMonkey platform. Descriptive statistics and frequency tables were analyzed using Stata 16.0. Results: Facebook was the most common access channel (96.4%), with users primarily visiting the site due to its credibility, to search for information on common health topics such as digestive diseases, cardiovascular issues, endocrine disorders, and dental health. Over 70% of participants reported searching for health information at least once per month. Most respondents preferred information from experts and scientific studies, favoring simple, easy-to-understand formats with multimedia integration. Around 53% expressed a desire for more content related to healthcare, disease prevention, nutrition, and specific illnesses. Conclusion: The study highlights a strong public demand for trustworthy, accessible, and regularly updated health information. Health & Life Newspaper should enhance interactive content, improve website interface, and incorporate personalized and multimedia formats to better meet the diverse information needs of the public in the digital era.